PENGARUH TERAPI MUSIK SUARA AIR MENGALIR DENGAN BRAINWAVE TERHADAP PENURUNAN TINGKAT DEPRESI PADA LANSIA DI RUMAH PELAYANAN SOSIAL LANJUT USIA WENING WARDOYO UNGARAN: THE EFECTS OF WATER SOUND MUSIC THERAPY WITH BRAINWAVE TO THE DECREASE OF DEPRESSION LEVELS IN ELDERLY IN THE HOUSE OF SOCIAL CARE FOR ELDERLY WENING WARDOYO UNGARAN - Pambudi, Hubertus Agung; Dewi, Christina Chintia; Anggraeni, Hesti (Stikes Wira Medika Bali, 2020)
Old age often accompanied by the declines in physical / biological conditions, psychological conditions, and changes in social and economic conditions, which will affect all aspects of life as well as their health. Depression is a mental health problem that often arises in the elderly. The purpose of this study was to determine whether there was an effect of providing music therapy with sound water flowing with brainwave on the level of elderly depression in Wening Wardoyo Ungaran Elderly Social Services House. This research is a quantitative study with a pre-experimental design design using a one group pretest-posttest design approach. Sampling uses total sampling with a sample of 31 respondents. The instrument used in this study to assess the level of depression in the elderly is the Geriatric Depression Scale (GDS) questionnaire. This research was conducted for 3 days in the morning and evening for 15 minutes.This research uses Marginal Homogeneity test. This study shows a significant effect of the Marginal Homogeneity test, which is p value 0.003, which means p <0.05. There is an Effect of giving Music Therapy Sounds of Flowing Water with Brainwave to the Decreased Depression Level in the Elderly in Wening Wardoyo Ungaran Elderly Social Services Home.